PENGARUH LATIHAN MENGGELINDING DAN MENENDANG BOLA TERHADAP KETERAMPILAN PASSING PADA CLUB SEPAK BOLAPROLITA U-12 SELATPANJANG - Rahmat, Pandi; Zainur, Zainur; Alimandan, Alimandan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Based on field observations made by researchers, there are several problems or phenomena that occur in Prolita U-12 Selatpanjang football, namely the lack of mastery of ball playing techniques such as passing. When passing, players make many mistakes, such as not being right, the ball is too slow and many balls do not arrive, so the ball is very easy to control and be controlled by the opponent, far from possession of the ball so that it falls and benefits the opponent. The purpose of this study was to determine the effect of rolling and kicking the ball on the passing skills of the Selatpanjang Prolita U-12 soccer club. The population in this study were 16 people. In connection with the population that is not so large and is still within the ability of the researcher, the entire population is used as a sample (total sampling) so that the total sample in the research conducted is 16 people. The instrument in this research is the implementation of the passing test. The results obtained were analyzed using the t-test. Based on the results above, it can be concluded that the effect of rolling and kicking the ball on the passing skills of the Selatpanjang Prolita U-12 soccer club. This shows that these rolling and kicking game exercises can be used to improve passing skills.Key Words: Rolling And Kicking Practice, Passing Skills